2018
DOI: 10.1097/md.0000000000012583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcatheter closure, mini-invasive closure, and open-heart surgical repair for treatment of perimembranous ventricular septal defects in children

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
10
0
2
Order By: Relevance
“…Recently, the emergence of transcatheter closure of pmVSD has been attracting considerable attention. Intervention closure offered several such as advantages rapid recovery, less trauma, less need for blood transfusion, shorter duration of hospital stay, and fewer complications [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the emergence of transcatheter closure of pmVSD has been attracting considerable attention. Intervention closure offered several such as advantages rapid recovery, less trauma, less need for blood transfusion, shorter duration of hospital stay, and fewer complications [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that the QOL of children in the minimally invasive surgery group was higher than that of those in the traditional surgery group with respect to the scores of problems related to cardiac symptoms and their treatment, drug treatment, and perception of physical appearance (< 0.05). This may be related to traditional surgical procedures that use median sternotomy and cardiopulmonary bypass, which can cause more complications and leave a long scar after the operation, whereas minimally invasive surgery is characterized by less trauma, quick recovery time, and no large incision of a median sternotomy, cardiopulmonary bypass, and vascular-related injuries [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with CHD and their parents may have mainly considered whether the cardiac malformation was corrected and whether the symptoms of CHD were improved at the early stages after the operation. Both minimally invasive and traditional surgical treatments can achieve ideal treatment outcomes for improving children’s hemodynamics [ 32 , 33 ]. At 12–36 months after the operation, children in the minimally invasive surgery group scored higher than those in the traditional surgery group ( p < 0.05), indicating that with the correction of cardiac malformation and recovery of cardiac function, the focus of children with CHD and their parents’ perception of their QOL began to shift toward their physical appearance, and permanent scarring was an important factor affecting the QOL at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional treatment for VSDs is surgical repair via cardiopulmonary bypass, which has the disadvantages of large surgical trauma, a long recovery time, and scarring [ 2 ] . Another common treatment is transcatheter device closure of the VSD, which has the advantages of no incision and a fast recovery; however, radiation exposure is required [ 3 ] . In recent years, transthoracic device closure has been widely used to treat VSDs in China.…”
Section: Introductionmentioning
confidence: 99%